De novo head and neck cancer arising in solid organ transplantation recipients: The Asan Medical Center experience. Issue 4 (August 2018) - Park, Marn Joon; Roh, Jong-Lyel; Choi, Seung-Ho; Nam, Soon Yuhl; Kim, Sang Yoon; Lee, Yoon Se
Abstract: Objective: De novo cancers of head and neck area in solid organ transplantation recipients show standardized incidence ratio (SIR) of 3.8. Immunosuppression following transplantation is suggested to play as a crucial factor in pathogenesis of secondary malignancy. Prognosis of head and neck cancer arising in solid organ transplantation recipients is proven to have poor prognosis. The incidence, risk, prognosis, and survival of de novo malignancy of head and neck area in solid organ transplantation recipients in single-tertiary medical center followed up for 20 years. Methods: A retrospective medical record review of the patients who received solid organ transplantation in Asan Medical Center from 1997 to 2016 was conducted. Patients confirmed as de novo malignancy in the head and neck area after organ transplantation were included, and presented as in the case-series format. Patients with previous history of head and neck malignancy, irradiation history of head and neck area, cutaneous malignant lesion, hematopoietic malignant lesion, malignancy of thyroid and parathyroid gland and metastatic lesions newly developed in head and neck area were excluded. The incidence of head and neck malignancy in South Korea were reviewed from the National Cancer Information Center of South Korea. For the statistical analysis, standardized incidence ratio (SIR) was obtained with 95% confidence interval. Results: Solid organ transplantation recipients show 20 times higher incidence of de novo cancer of head and neck area compared to general population. Of 13 de novo head and neck malignancy arising after solid organ transplantation, 2 (15.4%) patients were unable to withstand definitive management due to poor general condition. 2 (15.4%) patients had loco-regional recurrence, 1 (7.7%) patient with distant metastasis, and 3 (23.1%) patients died of cancer progression. Conclusion: Immunosuppression following solid organ transplantation gives a twenty-fold increased risk for the development of de novo head and neck cancer. A more precise and frequent checkup on head and area should be planned, suggesting a multi-disciplinary approach in combination with organ transplantation team.